Comparison of blockchain vs. centralised IT infrastructure costs for food traceability: a Thai broiler supply chain case study - Suchit Pongnumkul; Patcharawadee Ittipornpaisarn; Suporn Pongnumkul (Journal of Innovation and Entrepreneurship)
Abstract A robust food traceability system is crucial for ensuring seamless information flow within supply chains. While the current centralised approach, typically led by a supply chain leader, facilitates information exchange, it faces significant limitations, such as prolonged tracing processes and a lack of transparency. Blockchain technology presents a promising solution to address these challenges. However, concerns persist about the costs of IT infrastructure required to operate blockchain-based systems. This research compares the costs between centralised and blockchain ecosystems, focusing on the total cost for the entire industry, using the Thai broiler supply chain as a case study. We analysed both centralised and blockchain IT models, selecting 13 deployment scenarios for comparison. The Thai broiler supply chain provided data on IT infrastructure usage, with Monte Carlo simulation employed to address undisclosed supply chain data. The IT infrastructure costs for each scenario were calculated and compared. The analysis reveals a significant finding: blockchain implementation results in approximately 43% lower infrastructure costs compared to the practical centralised approach. This cost-effectiveness suggests that third parties, such as government bodies or central regulatory agencies, could play a crucial role in supporting the transition from centralised to blockchain-based food traceability systems, thereby enhancing supply chain transparency, efficiency, and food safety.